Management of Synchronous Locally Advanced Oropharyngeal Carcinoma and Early-Stage Esophageal Carcinoma in a Tertiary Cancer Center: A Case Report - A, Dharmaraj; Singh, Sharad; Singh, Rumita; Manna, Sumanta; Fatima, Tazyeen (Asian Pacific Journal of Cancer Care, 2023)
Background: Risk factors for squamous cell carcinomas (SCCs) of the head and neck (HN) and esophagus are similar, making synchronous primary tumors in these areas not entirely uncommon. Definitive chemoradiation (CRT) is the standard of care for locally advanced HNSCC and is a preferred option for inoperable esophageal SCC. Simultaneous treatment of both primaries with CRT can present technical challenges. Case Presentation: We report a case of synchronous oropharyngeal and esophageal SCC primary tumors that were treated simultaneously with definitive chemoradiotherapy.